La place du groupe de pairs dans l’intégration des nouvelles aides-soignantes dans les EHPAD - François Aubry (Sociologies, 2010)
This paper proposes a problematization of the integration of nursing’s aides in organizations like geriatric nursing homes in France, from the theoretical premise of “habilitation”, defined by Marcelle Stroobants. Becoming a nursing’s aides not only the continuous extension of training, acquisition of a diploma and getting a job. The process of integrating new nursing’s aides in the organization is a fundamental informal stage in the fact of entering the profession. Through analysis of twenty-four biographical interviews, we could note the contradiction between what actors speech, offering a vision of naturalized career choice, and the story of their careers. This discrepancy highlights the importance of the process of identity construction by the peer group. The different sociological approaches to the jurisdiction do not offer a vision as comprehensive as the “habilitation”, allowing a reversal of the individualistic perspective of training. In line with this theory, we will insist on the centrality of peer’s judgment, confer jurisdiction to this profession strongly dominated socially.